INTEGRATION OF THEORY AND PRACTICE IN DUAL EDUCATION (International journal of artificial intelligence, 2025)
The article discusses the essence of the dual education system, its role and importance in increasing the efficiency of the educational process through the integration of theory and practice. It also analyzes the specific aspects of the mechanisms of cooperation between industrial enterprises and educational institutions, and the issues of forming professional competencies in students in this process.